(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
A total of 60 pigeon, Columba livia (25 males and 35 females) were examined to observe helminth parasite infection. All the birds were found to be infected by eleven species of helminth parasites: four species of trematoda: Echinostoma revolutum (15%) E. trivolvus (5%), Patagifer bilobus (5%), Ehinoparyphium recurvatum (8.33%); six species of cestoda: Hymenolepis columbae (63.33%), Raillietina echinobothrida (100%), R. bonini (43.33%), R. cesticillus (100%), Cotugnia celebesensis (68.33%), C. cuneata (100%); and one species of nematoda: Ascaridia columbae (28.33%). Females showed slightly higher intensity of infestation than the males. Trematode parasites were found in intestine and rectum, cestode parasites were found in duodenum and intestine, nematode parasite Ascaridia columbae was found in caeca. Oesophagus, crop, proventriculus, gizzard, gallbladder, liver, kidney and muscles were free of parasites. Considering among seasons highest intensity of infection was found in autumn. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15324 J. Asiat. Soc. Bangladesh, Sci. 38(1): 93-98, June 2012